2010
DOI: 10.3109/17483107.2010.534231
|View full text |Cite
|
Sign up to set email alerts
|

Using Lego robots to estimate cognitive ability in children who have severe physical disabilities

Abstract: Children with severe physical disabilities can control a Lego robot to perform un-structured play tasks. In some cases, they were able to display more sophisticated cognitive skills through manipulating the robot than in traditional standardised tests. Success with the robot could be a proxy measure for children who have cognitive abilities but cannot demonstrate them in standard testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 13 publications
0
31
0
10
Order By: Relevance
“…The positive role of robotic technologies in sustaining the cognitive, affective and social development of children with different types of special educational needs through play has been confirmed by numerous studies in this sector (Marti & Giusti, 2009;Cook, Adams, Volden, Harbottle & Harbottle, 2011;Pearson & Borenstein, 2013;Robins & Dautenhahnn, 2014). Those studies used prototypes specifically built to be utilised by children with physical and cognitive disabilities or those affected by autism (Kaspar, Paro, IROMEC and NAO) Shibata et.…”
Section: State Of the Artmentioning
confidence: 91%
See 1 more Smart Citation
“…The positive role of robotic technologies in sustaining the cognitive, affective and social development of children with different types of special educational needs through play has been confirmed by numerous studies in this sector (Marti & Giusti, 2009;Cook, Adams, Volden, Harbottle & Harbottle, 2011;Pearson & Borenstein, 2013;Robins & Dautenhahnn, 2014). Those studies used prototypes specifically built to be utilised by children with physical and cognitive disabilities or those affected by autism (Kaspar, Paro, IROMEC and NAO) Shibata et.…”
Section: State Of the Artmentioning
confidence: 91%
“…The link with assistive technologies (e.g. robotic prosthetic limbs that enable children with physical disability to play with Lego bricks) is evident (Cook et al, 2011).…”
Section: Types Of Social Robotsmentioning
confidence: 99%
“…Both traditional and newly developed psycho-educational assessments are now available electronically, and technology has enabled other instruments to be modified for use with children with significant motor impairments (Warschausky et al, 2012). Robotherapy is another growing field with demonstrated potential for estimating cognitive ability of children whose impairments impede assessment by more conventional means (Cook, Adams, Volden, Harbottle, & Harbottle, 2011).…”
Section: The Impact Of Technologymentioning
confidence: 99%
“…No studies were found where children with physical disabilities programmed robots, but children with physical disabilities have used Lego robots to manipulate objects in play activities [12]. A commercial infrared (IR) remote controller for the RCX Lego robot was adapted so that children could use single switches to control a car-like robot using direct motor commands (e.g., to go forward or turn) or to run pre-stored programs.…”
Section: Introductionmentioning
confidence: 99%